ENTERPRISE POTENTIAL MANAGEMENT ON THE BASIS OF CUSTOMER-ORIENTED MARKETING - POLISHCHUK, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The essence and features of application of client - oriented marketing tools in potential management of industrial enterprises are revealed. It is proved that the development of market infrastructure transforms approaches to obtaining both resources and competitive advantages. It is emphasized that crowdfunding tools can justify and optimize marketing decisions, aggregate information, experience, opinions, forecasts, preferences and assessments, and on this basis to produce new ideas for modernizing the range of industrial products, methods of interaction with stakeholders and market organization. . It is concluded that the strategy of "crowd as a partner" involves the management of the crowd, a wide range of people united in the community and helps to attract intellectual and creative resources in solving marketing problems. This in turn involves the implementation of a crowdsourcing project. Crowdsourcing projects have become widespread in the practice of marketing activities. Their application will be appropriate and effective in managing the marketing potential of light industry enterprises. In addition to the fact that the company is able to solve its own marketing problems in research, product development, design, new proposals, it also gets a powerful platform to promote the brand name and create the desired socially oriented image of the company to develop innovation, improve and develop products. innovation.